Objection to Conscience: An Argument Against Conscience Exemptions in Healthcare - Giubilini, Alberto (Bioethics, 2017)
I argue that appeals to conscience do not constitute reasons for granting healthcare professionals exemptions from providing services they consider immoral (e.g. abortion). My argument is based on a comparison between a type of objection that many people think should be granted, i.e. to abortion, and one that most people think should not be granted, i.e. to antibiotics. I argue that there is no principled reason in favour of conscientious objection qua conscientious that allows to treat these two cases differently. Therefore, I conclude that there is no principled reason for granting conscientious objection qua conscientious in healthcare. What matters for the purpose of justifying exemptions is not whether an objection is ‘conscientious’, but whether it is based on the principles and values informing the profession. I provide examples of acceptable forms of objection in healthcare.